Gambaran Adversity Quotient pada Perawat - Tri Ajeng Alkarimah; Siti Nur'aini (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2022)
Adversity Quotient (AQ) is a measurement of a person's ability to respond to challenges or difficulties in life in order to achieve success. Nurses are one of the professions that require AQ to maximize performance as one of the largest service providers in hospitals. Nurses have a role in carrying out their duties in accordance with their rights and authorities. The main role of nurses is to provide services in the form of nursing care directly to patients, by providing comfort and a sense of security, trying to restore patient health, and facilitating patients in the healing process, so it is important to know AQ in order to see to what extent nurses are able to face difficulties. and barriers to work. The purpose of this study was to determine the AQ description of 114 nurses, who worked in a hospital in Jember Regency and obtained 84 people as a sampling. This research design uses descriptive quantitative method. Data collection using the Adversity Response Profile Quick TakeTM scale (ARP; 20 items) (Stoltz, 2005). The results showed that nurses had AQ tendencies with the largest percentage in the campers category, namely 51% with 43 nurses, which means nurses tend to prefer jobs that are simpler, easier, and less risky, and tend to be satisfied with their current jobs.